2023
DOI: 10.1111/all.15970
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in the epidemiology of drug allergy

Immaculada Doña,
Maria Jose Torres,
Gulfem Celik
et al.

Abstract: Drug allergy (DA) remains a complex and unaddressed problem worldwide that often deprives patients of optimal medication choices and places them at risk for life‐threatening reactions. Underdiagnosis and overdiagnosis are common and due to the lack of standardized definitions and biomarkers. The true burden of DA is unknown, and recent efforts in data gathering through electronic medical records are starting to provide emerging patterns around the world. Ten percent of the general population engaged in health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 171 publications
0
3
0
Order By: Relevance
“…Chronic diseases enhance the risk of DA due to impaired metabolism at kidney and liver [ 80 ]. Several studies reported that HRs are more common in children with cystic fibrosis (CF); particularly the frequency of BL HRs is higher.…”
Section: Risk Factors Related To the Hostmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic diseases enhance the risk of DA due to impaired metabolism at kidney and liver [ 80 ]. Several studies reported that HRs are more common in children with cystic fibrosis (CF); particularly the frequency of BL HRs is higher.…”
Section: Risk Factors Related To the Hostmentioning
confidence: 99%
“…The same results have been observed by Lalic M et al [ 128 ] who additionally demonstrated that high starting dose AEDs was another risk factor. Moreover, prolonged high dose repeated exposures after treatment suspension, are more likely to lead to HRs than a large single dose since they enhance immune recognition [ 80 , 129 ]. Finally, children are at special risks for HRs since unfriendly dosing formulations of drugs or miscalculation of some health care professional can lead to tenfold overdoses in administration of medicine.…”
Section: Risk Factors Related To the Drugmentioning
confidence: 99%
See 1 more Smart Citation